Sustainable Investment in Large Scale Rangeland Restoration (STELARR) - Magero, Chris (International Union for Conservation of Nature, 2023)
A presentation on Sustainable Investment in Large Scale Rangeland Restoration (STELARR), made at GEF-funded STELARR project meeting on a global rangelands data platform, developed by ILRI and partners.